DOI: 10.31274/rtd-180813-8752
|View full text |Cite
|
Sign up to set email alerts
|

Biological nutrient removal in bench-scale membrane bioreactor and full-scale sequencing batch reactor under various configurations and conditions

Abstract: for allowing me to take their valuable time. I must thank Dr. Ahmet YUCEER from Cukurova University, Turkey, who has always encouraged me to have a graduate degree in the U.S. Dr. Ertan ARSLANKAYA also deserves thanks for his critique of my work during the experimental stage as well as sharing his expertise in statistical analysis and kinetic modeling. Patrick Brown is also appreciated for his help in laboratory work. Finally, I would like to thank the Higher Education Council of Turkey for making available th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 100 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…The elimination of the clarifier also allows for operation of the system without regard to the settleability of the biomass and permits the HRT to be controlled completely independently of the SRT (Visvanathan et al, 2000). Many MBRs are operated at a relatively high SRT of 20-30 days, although it is possible to operate at very high SRTs of up to 75 days and maintain satisfactory treatment performance (Ahn et al, 2003;Ersu, 2006;Zhang et al, 2006). Operation at high SRT lowers sludge production and reduces the associated costs for sludge disposal (Trussell et al, 2005).…”
Section: Biological Nutrient Removal Using a Membrane Bioreactormentioning
confidence: 99%
See 4 more Smart Citations
“…The elimination of the clarifier also allows for operation of the system without regard to the settleability of the biomass and permits the HRT to be controlled completely independently of the SRT (Visvanathan et al, 2000). Many MBRs are operated at a relatively high SRT of 20-30 days, although it is possible to operate at very high SRTs of up to 75 days and maintain satisfactory treatment performance (Ahn et al, 2003;Ersu, 2006;Zhang et al, 2006). Operation at high SRT lowers sludge production and reduces the associated costs for sludge disposal (Trussell et al, 2005).…”
Section: Biological Nutrient Removal Using a Membrane Bioreactormentioning
confidence: 99%
“…Ahn et al (2003) reported total nitrogen removal of 60% and total phosphorus removal of 93% at 70 days SRT. Ersu (2006) investigated SRTs from 10 to 75 days using synthetic municipal wastewater and reported optimum performance (78% TN, 81% TP removal) at an SRT of 50 days. Innocenti et al (2002) reported promising MBR performance (85% TN, 89% TP removal) at an SRT of 190 days.…”
Section: Impact Of Srt On Bnr Performancementioning
confidence: 99%
See 3 more Smart Citations